EMOTION REGULATION AS AN AFFECTIVE DIMENSION OF PEDAGOGIC COMPETENCE IN INCLUSIVE EDUCATION - Murnia Safinatu; Muryanti; M. Jaya Adi Putra (International Journal of Educational Best Practices, 2026)
This study aims to analyze the regulation of emotions as part of the affective dimension of tutor pedagogic competence in the implementation of inclusive education at PKBM Bina Kreasi Pekanbaru City. This study adopts a qualitative approach with a descriptive research design. The research was conducted at PKBM Bina Kreasi in Pekanbaru. The research subjects consisted of individuals involved in the implementation of educational programs at the institution. Data were collected through observation, interviews, and documentation. Data analysis was carried out using NVivo 12 Plus software, which included stages of data import, coding, data visualization, and theme identification and development. The results of the study show that the regulation of tutors' emotions is reflected in the aspects of empathy, patience, self-control, and communication with inclusive students. With NVivo visualization, it shows the dominance of code in indicators of student characteristics mastery and student communication. Although tutors have shown quite good emotion regulation skills, there are obstacles in the form of limitations in special training, communication with students, and a lack of professional assistance. These findings imply the need for targeted professional development programs, improved communication strategies, and greater institutional support to enhance the effectiveness of inclusive learning practices.